Study the Synthesis and Produce Silver Nanoparticles and their Antibacterial Role (Subject Review) - Abdullah, Salam Khalid Mutlag (American Journal of Botany and Bioengineering, 2025)
Nanotechnology is a branch of technology that uses materials having at least one dimension between 1 nm and 100 nm to generate new materials and products. Nanomaterials are very different from macroscopic materials and have only recently caught the interest of researchers because of their unique, superior, and significant properties. Two significant distinctions are their high surface-to-volume ratio and the higher concentration of atoms at grain boundaries. Materials such as metal, metal oxide, carbon nanomaterials have been widely exploited as new antibacterial agents because of their small sizes, unique chemical and physical characteristics, and high specific surfaces. Silver nanoparticles have been widely used in sectors like biomedicine, pharmacy, and cosmetics because of their special antibacterial properties. Because of their broad-spectrum antimicrobial qualities and potent antibacterial efficacy against a variety of bacteria, viruses, and fungi, Silver (Ag) nanoparticles are the most commonly employed antibacterial nano-agent among the different manufactured nanoparticles that are used in antibacterial therapies.